A melanoma immune response signature including Human Leukocyte Antigen‐E. (9th October 2013) - Tremante, Elisa; Ginebri, Agnese; Lo Monaco, Elisa; Benassi, Barbara; Frascione, Pasquale; Grammatico, Paola; Cappellacci, Sandra; Catricalà, Caterina; Arcelli, Diego; Natali, Pier Giorgio; Di Filippo, Franco; Mottolese, Marcella; et al.
Summary Paired cultures of early‐passage melanoma cells and melanocytes were established from metastatic lesions and the uninvolved skin of five patients. In this stringent autologous setting, cDNA profiling was used to analyze a subset of 1477 genes selected by the Gene Ontology term 'immune response'. Human Leukocyte Antigen E (HLA‐E) was ranked 19th among melanoma‐overexpressed genes and was embedded in a transformation signature including its preferred peptide ligand donors HLA‐A, HLA‐B, HLA‐C, and HLA‐G. Mostly undetectable in normal skin and 39 nevi (including rare and atypical lesions), HLA‐E was detected by immunohistochemistry in 17/30 (57%) and 32/48 (67%) primary and metastatic lesions, respectively. Accordingly, surface HLA‐E was higher on melanoma cells than on melanocytes and protected the former (6/6 cell lines) from lysis by natural killer (NK) cells, functionally counteracting co‐expressed triggering ligands. Although lacking HLA‐E, melanocytes (4/4 cultures) were nevertheless (and surprisingly) fully protected from NK cell lysis.